2002
DOI: 10.1590/s0100-29452002000300055
|View full text |Cite
|
Sign up to set email alerts
|

Pupunha no mercado de Manaus: preferências de consumidores e suas implicações

Abstract: PEACH PALM IN MANAUS, MARKET AMAZONAS, BRAZIL: CONSUMER PREFERENCES AND THEIR IMPLICATIONSABSTRACT -The demand for fresh fruit of peach palm (Bactris gasipaes Kunth) has remained stable through 50 years of research and promotion in the Brazilian Amazon. Interviews with 30 consumers at the principal market in Manaus, Amazonas, during the second harvest determined that red (by 53%), medium weight (67%), moderately oily fruit (53% oily and 40% moderately oily), in large bunches (50%) with a reasonable price (R$5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 1 publication
1
9
1
9
Order By: Relevance
“…In general, consumers prefer red fruits to yellow ones and oily fruits to starchy ones ). Clement and Santos (2002) confirmed those findings through an analysis of consumer preferences for peach palm in Manaus, Brazil. They found that consumers prefer red, moderately oily fruits of medium weight.…”
Section: Multiple Uses Of Peach Palmsupporting
confidence: 80%
See 3 more Smart Citations
“…In general, consumers prefer red fruits to yellow ones and oily fruits to starchy ones ). Clement and Santos (2002) confirmed those findings through an analysis of consumer preferences for peach palm in Manaus, Brazil. They found that consumers prefer red, moderately oily fruits of medium weight.…”
Section: Multiple Uses Of Peach Palmsupporting
confidence: 80%
“…Market demand for freshly cooked fruit is estimated at about 20,000 t per year in Colombia, and the demand is increasing . In Brazil market studies on peach palm show that the demand for fresh fruit has remained stable during the past 50 years (Clement and Santos 2002). However, reports of overproduction have come from Colombia and Brazil (Clement and Santos 2002;Godoy et al 2007).…”
Section: Socio-economic Aspects Of Peach Palmmentioning
confidence: 99%
See 2 more Smart Citations
“…Com esse objetivo, farinhas e farelos de diferentes grãos e tubérculos como arroz, cevada, milho, trigo, mandioca Produção de amilase por rizóbios, usando farinha de pupunha como substrato e batata têm sido usadas no meio de cultura para aumentar a produtividade de amilases de fungos e bactérias 12,13,27 . Palmeira nativa dos trópicos americanos, a pupunheira (Bactris gasipaes Kunth) produz frutos comestíveis de alto valor nutritivo 39 , os quais estão completamente integrados à dieta alimentar dos amazônidas 8,22 . Os frutos são consumidos cozidos e prestam-se à extração de óleo ou à produção de farinhas para as mais variadas finalidades 10 .…”
Section: Introductionunclassified